Preliminary phytochemical screening and thin layer chromatography of polyherbal antidiabetic extracts - BIJU T FRANCIS,; SUDHA S, (International Journal of Pharma and Bio Sciences, 2017)
Herbal medicines are used therapeutically all around the world and the use of medicinal plants for management of diseases is probably the oldest existing method that humanity tries to handle the illness. Herbal medicinal products are considered to be free from side effects and less toxic on comparison with synthetic drugs. However, screening of plants for their activities is very essential to evaluate the actual medicinal value of each plant. The plant medicinal value lies in some chemical substances that produce a definite physiological or pharmacological action on the human body such as alkaloids, tannins, flavonoids, saponins etc. Diabetes mellitus has become a serious threat to human life that continues to increase in numbers and its complications impose significant consequences on individuals, families, health systems and countries. Multifactorial metabolic diseases develop several complications like hyperlipidemia, hepatic toxicity, immunodeficiency etc. and hence, instead of mono-drug therapy, the management of the disease requires the combination of herbs that will provide a synergic effect. The present study evaluates the phytochemical constituents of seven anti-diabetic medicinal plants used in traditional medicine by performing chemical tests and thin layer chromatographic studies using various solvent systems. The polyherbal combination of Phyllanthus emblica (fruit), Phyllanthus amarus (whole plant), Tinospora cordifolia (whole plant), Curcuma longa (Rhizome), Syzygium aromaticum (flower), Piper lognum (fruit) and Moringa oleifera (leaf) are used for the phytochemical evaluation.